Pollution haven hypothesis (PHH) - Burcu Ozcan (Elgar Encyclopedia of Energy Economics, 2025)
Context The Centers for Disease Control and Prevention's (CDC) National Program of Cancer Registries (NPCR) supports the management and operations of central cancer registries (registries) across the United States through funding and technical assistance (TA). Objective To examine barriers and facilitators to program evaluation among NPCR-funded cancer registries, assess registries' TA needs related to evaluation and implementation, and evaluate satisfaction with CDC-provided TA. Design and setting We used a mixed-methods approach. Quantitative analysis examined 114 TA requests submitted between June 2022 and September 2023 through an administrative TA management platform. Qualitative data were collected during routine monthly check-in calls with 23 registries from October 2023 to January 2024, during which evaluators facilitated conversations on program evaluation experiences, TA needs, and satisfaction. Participants TA requests submitted by 32 cancer registries and routine check-in calls with 23 registries, representing 38 unique registries across data sources. Main outcome measures Cancer registry program evaluation barriers and facilitators, TA needs, and satisfaction with CDC-provided TA. Results Most TA requests addressed operations and reporting (69.3%), followed by data submission (15.8%), evaluation and data management plans (8.8%), education and training (5.3%), and registry software/informatics (0.9%). Among resolved requests, more than 75% were addressed within 7 days. Qualitative findings indicated that registries were generally satisfied with TA timeliness and quality. Barriers to program evaluation included limited resources, insufficient training, and leadership transitions. Facilitators included adequate staffing and funding, evaluation competency, strong partnerships, and effective registry operations. Registries identified overlapping TA needs related to organizational support, targeted expertise, guidance and expectations, training, technical infrastructure, and peer learning. Conclusions Program evaluation capacity within cancer registries is shaped by resources, training, partnerships, and operational context. Findings highlight opportunities for TA providers to strengthen evaluation through targeted training, clearer guidance, and peer learning to support consistent program implementation across multisite public health programs.